Linking Industry 4.0 Technologies to Organizational Performance through Human Skill Capabilities - Erna Wati; Iskandar Itan; Teddy Jurnali; Sheila Septiany; Erliani (Institut Bisnis dan Informatika Kesatuan, 2026)
The Fourth Industrial Revolution (Industry 4.0) is transforming industries worldwide through advanced technologies such as cyber-physical systems, big data analytics, cloud computing, robotics, 3D printing, and augmented reality. This study examines the relationship between Industry 4.0 adoption, human skill capabilities, and organizational performance. Using quantitative research design and survey-based data collection, the research investigates how technological integration and workforce competencies contribute to business outcomes. Findings reveal that Industry 4.0 technologies significantly enhance organizational performance, particularly in efficiency, productivity, and cost-effectiveness. However, the study also emphasizes that technological advancements alone are insufficient; skilled human capital is critical for effective implementation and management. Competent employees are essential to address challenges, optimize the use of new technologies, and sustain organizational growth. The results highlight the need for organizations to balance investments in technology with workforce development, ensuring employees can adapt to rapid changes in the industrial landscape. This study contributes to both theory and practice by demonstrating that aligning technological progress with human capability development is vital for organizations to enhance performance and maintain competitiveness in the Industry 4.0 era.